2022
DOI: 10.3390/f13091526
|View full text |Cite
|
Sign up to set email alerts
|

Before Becoming a World Heritage: Spatiotemporal Dynamics and Spatial Dependency of the Soundscapes in Kulangsu Scenic Area, China

Abstract: Kulangsu is a famous scenic area in China and a World Heritage Site. It is important to obtain knowledge with regard to the status of soundscape and landscape resources and their interrelationships in Kulangsu before it became a World Heritage. The objective of this study was to explore the spatial dependency of the soundscapes in Kulangsu, based on the spatiotemporal dynamics of soundscape and landscape perceptions, including perceived sound sources, soundscape quality, and landscape satisfaction degree, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Soundscape construction is considered a new trend of thought that stimulates the potential of designers [15][16][17][18] and challenges the traditional dominance of vision in today's space design. Previous studies have conducted soundscape change [19][20][21][22], quality assessment [23,24], spatial correlation [25], and restoration research [26] for different spatial environments. In terms of sound scene preferences, the difference in sound source types [27], sound source preferences, and perception experiences [28] have been the focus of attention in previous research.…”
Section: Introductionmentioning
confidence: 99%
“…Soundscape construction is considered a new trend of thought that stimulates the potential of designers [15][16][17][18] and challenges the traditional dominance of vision in today's space design. Previous studies have conducted soundscape change [19][20][21][22], quality assessment [23,24], spatial correlation [25], and restoration research [26] for different spatial environments. In terms of sound scene preferences, the difference in sound source types [27], sound source preferences, and perception experiences [28] have been the focus of attention in previous research.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the research results of Yu et al, i.e., a sufficient number of sports fields on campus can promote college students’ dynamic exercise behaviors ( 44 ). Some studies on community common spaces have shown that fitness facilities in common spaces can better promote dynamic exercise behaviors than activity fields ( 64 ). This discrepancy is mainly due to different research groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the highest classification accuracy was achieved via the random forest methodology. Some authors have noted that due to its strong anti-noise ability and high stability, the random forest methodology is the most widely used in the classification research of forestry and agriculture [33,34]. It can usually achieve greater classification accuracy and can classify and count high-dimensional data while ensuring the randomness of samples.…”
Section: Discussionmentioning
confidence: 99%